The Rahman-Nat diffraction on a thin laser-induced grating of the refractive index in semiconductors - Semchuk, O.Yu.; Gichan, О.І.; Grechko, L.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
Studied in this work is the Rahman-Nat diffraction on a thin grating of refractive index in semiconductor, which was created by an interference pattern of two coherent laser beams. Numeral calculations showed that the maximal diffraction efficiency for the Rahman-Nat diffraction in the first order was 28.2 % for a purely phase grating at its thickness z ~ 200, and 4.8 % for a purely amplitude grating. It was also ascertained, that waves belonging to the nearby diffraction orders differ from each other by π/2 in their phase.